2016
DOI: 10.1007/s00412-016-0600-y
|View full text |Cite
|
Sign up to set email alerts
|

Slx4 scaffolding in homologous recombination and checkpoint control: lessons from yeast

Abstract: Homologous recombination-mediated DNA repair is essential for maintaining genome integrity. It is a multi-step process that involves resection of DNA ends, strand invasion, DNA synthesis and/or DNA end ligation and, finally, the processing of recombination intermediates such as Holliday junctions or other joint molecules. Over the last 15 years, it has been established that the Slx4 protein plays key roles in the processing of recombination intermediates, functioning as a scaffold to coordinate the action of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 119 publications
(191 reference statements)
1
13
0
Order By: Relevance
“…The catalytic subunits Rad1 and Slx1 relocalized to subnuclear foci in a high percentage of cells after MMS treatment (Figures 2A and 2B), similar to Mus81. Likewise, Slx4, which is not only a subunit of Slx1-Slx4, but is also a platform for several proteins involved in genome integrity maintenance (Cussiol et al, 2017), formed foci upon exposure to MMS (Figures 2A and 2B), in agreement with previous data (Tkach et al, 2012). As for Mus81-Mms4, the accumulation of Rad1, Slx1, and Slx4 into foci was not due to increased protein levels upon DNA damage (Figures S1D-S1F), thus reflecting relocalization.…”
Section: Structure-specific Endonucleases Colocalize To Foci Followinsupporting
confidence: 90%
See 1 more Smart Citation
“…The catalytic subunits Rad1 and Slx1 relocalized to subnuclear foci in a high percentage of cells after MMS treatment (Figures 2A and 2B), similar to Mus81. Likewise, Slx4, which is not only a subunit of Slx1-Slx4, but is also a platform for several proteins involved in genome integrity maintenance (Cussiol et al, 2017), formed foci upon exposure to MMS (Figures 2A and 2B), in agreement with previous data (Tkach et al, 2012). As for Mus81-Mms4, the accumulation of Rad1, Slx1, and Slx4 into foci was not due to increased protein levels upon DNA damage (Figures S1D-S1F), thus reflecting relocalization.…”
Section: Structure-specific Endonucleases Colocalize To Foci Followinsupporting
confidence: 90%
“…At the same time, these proteins need to be tightly controlled to avoid the unscheduled cleavage of DNA intermediates, which could lead to genomic instability due to chromosomal rearrangements, high levels of chromatid exchanges, or faulty replication. These controls are achieved by different regulatory mechanisms that include posttranslational modifications and interactions with other factors that stimulate their activity (Cussiol et al, 2017;Dehé and Gaillard, 2017;Minocherhomji and Hickson, 2014;Sarangi and Zhao, 2015;West et al, 2015). For example, in budding yeast and human cells, the activity of the endonuclease Mus81-Mms4/EME1 is strictly regulated by cyclin-dependent kinase (CDK)-and polo-like kinase (PLK)dependent phosphorylation of the non-catalytic subunit Mms4/ EME1 (Gallo-Ferná ndez et al, 2012;Matos et al, 2011;Saugar et al, 2013;Szakal and Branzei, 2013) and, in fission yeast, by CDK-dependent phosphorylation of Eme1 (Dehé et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In both yeast and humans, DNA damage signaling kinases phosphorylate proteins in homologous recombination (HR)‐directed repair and have been shown to play an important regulatory role. For example, Mec1 phosphorylates Rtt107, Slx4, and Sgs1, all of which are known to play multiple roles in HR‐mediated repair, from the control of resection to the dissolution or resolution of joint chromosome structures (Sarbajna & West, ; Hang & Zhao, ; Cussiol et al , ; Guervilly & Gaillard, ). Recent work from our laboratory has revealed that phosphorylation of these proteins correlates with the ability of cells to suppress GCRs, suggesting that proper control of HR repair is essential for preventing chromosomal rearrangements (Lanz et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The reversible nature of these modifications is important for turning off the DDR after DNA damage conditions are removed or adapted to. DDR dampening deficiency is also undesirable and can lead to prolonged cell cycle arrest and in extreme cases, cell death (3).…”
mentioning
confidence: 99%